Pengaruh Konformitas Teman Sebaya dan Kecerdasan Emosional terhadap Sikap Seks Pranikah pada Remaja - Oktavia Putri Damayanti; Maharani Ardi Putri; Hayu Wardani (Jurnal Ilmiah Psikologi MIND SET, 2014)
Pre-marital sex phenomenon in the recent society does not only occur among adults, but it also occurs among high school and junior school students. The tendency of teenagers for being engaged in pre-marital sex is getting high when they have positive attitude toward sexual behavior. The effort to vent sexual desire among teenagers is basically affected by external factors, which is peer conformity. Conformity to peers could effectively predict teenagers' difficulties in pro-social problem and dangerous behavior such as pre-marital sex. In addition to the external factors, the internal factor could be seen from emotional intelligence, in which the teenagers are required to properly control their emotion in dealing with sexual desire. This research is aimed to examine the effect of peer conformity and emotional intelligence on pre-marital sexual behavior among teenagers. The sample in this research consists of 114 early teenagers, who aged between 11-14 years old. The researcher used Multi-linear Regression as a technique of data analysis. The result of this research shows that peer conformity and emotional intelligence could significantly affect pre-marital sexual behavior among teenagers.